GA₃ 처리에 따른 유색칼라‘블랙매직’의 생육기간 동안 생장반응의 변화 - 최소라(So Ra Choi); 임회춘(Hoi Chun Lim); 안민실(Min Sil Ahn); 김명준(Myung Jun Kim); 유동현(Dong Hyun You); 류정(Jeong Ryu); 은종선(Jong Seon Eun) (Weon'ye gwahag gi'sulji, 2008)
유색칼라 ‘블랙매직’의 GA3 처리에 따른 생육기간 동안 생장반응을 보기 위하여 정식 전 괴경을 GA3 500mg･L-1 처 리구와 무처리구로 구분하여 정식 후 1~2개월 간격으로 생 장반응을 조사하였다. 초장은 정식 후 2개월까지 신속히 증 가하였고 10월 이후 잎이 노화하였다. 신초중과 엽수는 8월 에 가장 높았고 엽장은 6월 이후 거의 변화가 없었으며, 엽폭은 5월부터 8월까지 서서히 증가하였다. 괴경중은 정식 한 후 8월까지는 점차 감소하다가 그 후 12월까지 증가하였 다. 괴경경은 괴경중과 비슷하게 변화했으나 생육 초기의 감소현상이 나타나지 않았다. GA3 처리는 무처리에 비해 맹 아소요일수가 2.8일 단축되어 신초 발달이 양호하였으나 6 월 이후에는 초장, 신초중, 엽폭이 무처리에 비해 감소하였 다. GA3 처리는 무처리에 비해 개화수가 증가하였으나 화폭 은 감소하였으며 불염포의 기부가 열리는 경향이었다. 또한 GA3 처리를 하면 무처리에 비해 괴경의 비대가 적고 괴경 당 눈의 수도 적은 것으로 보아 이 괴경을 이듬해 재배하면 생육에 영향을 미칠 것으로 생각된다. The main objectives of this study were to investigate changes of growth responses during a growing period in Zantedeschia albomaculata ‘Black Magic’ by soaking tubers into a 500 mg･L-1 GA3 solution before planting. Plant grew very rapidly for two months after planting and the growth stopped with leaf senescence since October. Shoot weight and number of leaves were the highest on August, leaf length was similar since June and leaf width increased from May until August steadily. Tuber weight decreased from planting time until August and then increased until December. Also tuber diameter showed a similar change accord with tuber weight but decrease phenomenon in early growth stage was not shown. Days to emergence was 2.8 days shorter in GA3 treatment than no treatment, so shoot development was promoted for two months after planting, but plant height, shoot weight and leaf width in GA3 treatment were shorter since June. According to GA3, number of flowers increased, but leaf width tend to decrease. Flower width decreased and a lower of spathe opened. Also tuber weight and number of buds were decreased by GA3 treatment thus it was thought that growth response in the following year would be affected by GA3 treatment. KCI Citation Count: 1